Investigation of Minimal Channel Spacing in HDWDM Systems - Bobrovs, V.; Ivanovs, G. (Elektronika ir Elektrotechnika, 2009)
As WDM channel spacing continues to decrease in size, we demonstrate the minimal allowed channel spacing in HDWDM systems. According to experimental model we have created a simulation scheme in OptSim 5.0 software with the real parameters of all experimental devices. Our calculation have shown that, the minimal channel interval for 2.5 Gbit/s HDWDM system should be more than 0.2 nm, and for 10 Gbit/s system not less than 0.3 nm. These results open up new possibilities for HDWDM networks while pointing to new potential for management of optical spectrum as well as providing a limit of achievement for channel interval at different bit rates in the fiber optical network. Ill. 8, bibl. 10 (in English; summaries in English, Russian and Lithuanian).